Multi‐Sites Electrocatalysis in High‐Entropy Alloys - Li, Hongdong; Lai, Jianping; Li, Zhenjiang; Wang, Lei (Advanced functional materials, 2021)
High‐entropy alloys (HEAs) have attracted widespread attention in electrocatalysis due to their unique advantages (adjustable composition, complex surface, high tolerance, etc.). They allow for the formation of new and tailorable active sites in multiple elements adjacent to each other, and the interaction can be tailored by rational selection of element configuration and composition. However, it needs to be further explored in catalyst design, the interaction of elements, and the determination of active sites. This review article focuses on the important progress for multi‐sites electrocatalysis in HEAs. The classification is done on the basis of catalytic reaction, including hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, alcohol oxidation reaction, carbon dioxide reduction reaction, and nitrogen reduction reaction. Based on experiments and theories, a more in‐depth exploration of the high catalytic activity of HEAs will be conducted, including the selection of elements (the special role of each element in catalysis) and the multi‐sites effect. This review can provide the basis for the element selection and design of HEAs in some reactions, to adjust the compositions of HEAs to improve their intrinsic activity. Furthermore, the remaining challenges and future directions for promising research fields are also provided. A brief review of the recent progress in multi‐sites electrocatalysis of high‐entropy alloys, and the effect of various elements and their synergistic effects in different electrocatalytic reaction catalysts are analyzed, to gain a clearer insight into their active sites and rationally design high‐entropy alloys.